2020
DOI: 10.1038/s41467-020-18973-w
|View full text |Cite
|
Sign up to set email alerts
|

Pan-cancer analysis reveals TAp63-regulated oncogenic lncRNAs that promote cancer progression through AKT activation

Abstract: The most frequent genetic alterations across multiple human cancers are mutations in TP53 and the activation of the PI3K/AKT pathway, two events crucial for cancer progression. Mutations in TP53 lead to the inhibition of the tumour and metastasis suppressor TAp63, a p53 family member. By performing a mouse-human cross species analysis between the TAp63 metastatic mammary adenocarcinoma mouse model and models of human breast cancer progression, we identified two TAp63-regulated oncogenic lncRNAs, TROLL-2 and TR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…WDR26 is a component of the CTLH complex that is mutated or upregulated in many solid cancers [ 9 ]. WDR26 has not been implicated in blood cancers, yet its significance as therapeutic target in carcinomas has been recognized [ 10 ]. MTF2, an accessory unit of the PRC2 complex involved in gene repression and growth promotion of various cancers [ 11 ], is a validated molecular target in AML [ 12 ].…”
Section: To the Editormentioning
confidence: 99%
“…WDR26 is a component of the CTLH complex that is mutated or upregulated in many solid cancers [ 9 ]. WDR26 has not been implicated in blood cancers, yet its significance as therapeutic target in carcinomas has been recognized [ 10 ]. MTF2, an accessory unit of the PRC2 complex involved in gene repression and growth promotion of various cancers [ 11 ], is a validated molecular target in AML [ 12 ].…”
Section: To the Editormentioning
confidence: 99%
“…The specific mechanism by which NOLC1 contributed to tumorigenesis remains unclear. Intriguingly, it was recently reported that lncRNAs (TROLL-2 and TROLL-3) could counteract the interaction between WDR26 and NOLC1, while promoting the combination of WDR26 and AKT to activate the PI3K/AKT pathway in lung cancer cells, human breast carcinoma cells, and human melanoma cell lines [ 16 ]. PI3K/AKT pathway is dysregulated in various cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the coding gene GATA3 has a wide expression pattern in patients and breast cancer cell lines, as observed by RNA-Seq analysis. As previous studies have demonstrated, mRNAs tend to have less tissue-and stagespecific expression 41,58,59 in contrast to lncRNAs, which tend to have more tissue-specific 19,60,61 and stage-specific expression in disease, which is one of the main reasons lncRNAs have been proposed as molecular biomarkers in cancer. 16,62,63 Alternatively, results by receiver operating characteristic curve showed that GATA3 had sensitivity of 52.4% and specificity of 73.9% with an AUC of 0.60 in RT-qPCR expression analyses; the results suggest that GATA3 mRNA expression has low ability to distinguish responders from nonresponders to NAC due to its low sensitivity.…”
Section: Contreras-mentioning
confidence: 96%